Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1016/j.ctrv.2015.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Safety of cranial radiotherapy concurrent with tyrosine kinase inhibitors in non-small cell lung cancer patients: A systematic review

Abstract: Recently, non-small cell lung cancer (NSCLC) has been partly subclassified into molecularly-defined oncogene "addicted" tumors for which targeted agents are available. Tyrosine kinase inhibitors (TKI) are currently approved for patients with an activating epidermal growth factor receptor (EGFR) mutation or anaplastic lymphoma kinase (ALK) rearrangement. In these patients, brain metastases are often the first site of progression while on TKI treatment. The TKI may however still be active on extra-cranial sites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 62 publications
(201 reference statements)
0
19
0
Order By: Relevance
“…According to a systematic review reported by Hendriks et al . most of nine trials showed no increased neurotoxicity in TKI plus brain radiotherapy compared to TKI alone . Whereas, another retrospective study reported increase of memory impairment in TKI plus WBRT compared to TKI alone .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…According to a systematic review reported by Hendriks et al . most of nine trials showed no increased neurotoxicity in TKI plus brain radiotherapy compared to TKI alone . Whereas, another retrospective study reported increase of memory impairment in TKI plus WBRT compared to TKI alone .…”
Section: Discussionmentioning
confidence: 97%
“…According to a systematic review reported by Hendriks et al most of nine trials showed no increased neurotoxicity in TKI plus brain radiotherapy compared to TKI alone. 32 Whereas, another retrospective study reported increase of memory impairment in TKI plus WBRT compared to TKI alone. 17 Two randomized phase 3 studies of solid tumors with one to three BMs showed that SRS plus WBRT impaired health-related QOL and cognitive function, respectively, and did not improve OS compared to SRS alone.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that TKI can be considered as the first choice if the primary goal was to achieve prompt symptomatic relief. It is unclear whether delivery of concomitant radiotherapy can be resulted in better outcomes, but such an approach of combined treatment deserved additional studies to explore, considered of the favorable toxicity profile when radiotherapy combined with TKI therapy reported in literatures (20,21).…”
Section: Palliative Radiotherapy In Advanced Nsclc Treated With Egfr Tkimentioning
confidence: 99%
“…Concomitant use of TKI may have the advantage of a synergistic effect on the brain metastases, but at the price of possibly increased risk of neurotoxicity. Such attempt had been reported in a lot of retrospective and prospective studies, but often with small sample size (20). Primary outcomes in these studies varied and the data were measured and reported in a nonuniform way.…”
Section: Whole Brain Radiotherapy (Wbrt) and Stereotactic Radiosurgermentioning
confidence: 99%
“…The Oncologist 2016; 21:964-973 Implications for Practice: Stereotactic body radiation therapy (SBRT) or SBRT-like treatments are increasingly being used for oligoprogression in patients with oncogene-driven non-small cell lung cancer.This approach allows patients to extend the duration of tyrosine kinase inhibitor therapy and has the potential to prolong survival times. Careful patient selection and risk-adapted radiation dosing is of critical importance to minimize toxicity and preserve patient quality of life.The Oncologist 2016;21:964-973 www.TheOncologist.com ©AlphaMed Press 2016 reports on this topic [11][12][13][14][15].The reader is also referred to other recent reviews on the role of local therapies for patients with oligometastatic or oligoprogressive disease [16][17][18][19][20][21][22].…”
mentioning
confidence: 99%